Religión y Estado en el monacato oriental. Muhammad - Blázquez Martínez, José María (Gerión. Revista de Historia Antigua, 2008)
The Byzantine Empire had frequently relationship with the Oriental monks. The emperors, the empresses and the public officials of the Empire treated favourably the monks, but as well they interfered in typical ecclesiastical matters, like in the heresies, to put their willpower. Muhammad received many religion aspects fron the Oriental christian monasticism.